Twin specialization in legal and financial translation: links and training needs in Spain - Alcalde Peñalver, Elena (MonTi Monografías de Traducción e Interpretación, 2017)
In this article, a set of results from a doctoral thesis by the author is presented on the academic and professional situation of financial translation in Spain. The review of the literature on financial translation highlights the immense importance attached to specialization in the subject area of finance for professional practice. Nevertheless, the results of the survey distributed to financial translators, employers requiring financial translation services and teachers in charge of financial translation subject modules in Spanish Universities, as part of the empirical study completed in the doctoral thesis, showed that specialization in financial translation is linked to specialization in legal translation, due, among other factors to the existence of numerous hybrid texts that combine both fields. Training models in financial translation should therefore be combined with legal translation to respond to the observed market demands.